Банкротство мнимых ценностей: [роман] / Олег Рой - Рой Олег (Капризы судьбы, 2011)
Экземпляры: аб. (2012) / Инвентарный номер: 54185 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Р 65 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44